Impact of long-term sputtering on mirror samples fabricated from different kind tungsten - Voitsenya, V.S.; Bardamid, A.F.; Konovalov, G.V.; Makhov, M.N.; Ryzhkov, I.V.; Shapoval, A.N.; Skoryk, O.O.; Solodovchenko, S.I.; Stan’, A.F.; Zhou Zhang-jian; Zhao Ming-yue (Вопросы атомной науки и техники, 2016)
The results are presented on effects of long term sputtering of mirror-like samples made of pure tungsten and tungsten with dopants (Y, K-Al, La). The dynamics of surface relief and optical characteristics were measured depending on the depth of erosion under Ar ion bombardment; the rate of sputtering was estimated by the use of mass loss measurements. Difference was found in the character of surface relief, rate of degradation of reflectance and relation between specular and diffusive components of reflected light for different kind W samples.